Pengembangan Protokol Deteksi Staphylococcus aureus Berbasis Molekuler - Koentjoro, Maharani Pertiwi; Alviani, Melinda Nuril; Jatmiko, Yoga Dwi; Habibah, Laila Nur; Al Fatih, Ahmad Nuril Fuad; Kartikaningsih, Hartati (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Staphylococcus aureus becomes a normal flora in humans, especially on the skin and in the nose. However, if it becomes excessive or if there are pathogenic variants, it can cause various health problems. The purpose of the study is to develop a molecular-based detection method for Staphylococcus aureus using the norA primer gene. The norA gene in Staphylococcus aureus is known to play a role in pathogenesis with its antibiotic resistance ability. This type of research is analytical observational with a cross-sectional method. The methods in the study include the isolation and identification of Staphylococcus aureus from healthcare facility equipment. Isolation and identification include bacterial isolation using Blood Agar Plate (BAP) media; isolate purification, Gram staining; biochemical tests using Mannitol Salt Agar (MSA) media, glucose tests, Voges Proskauer (VP) tests, catalase tests, and coagulase tests. Furthermore, S. aureus isolates were tested using a molecular-based method, namely Polymerase Chain Reaction (PCR). This method includes DNA isolation stages, qualitative testing with agarose gel electrophoresis, semi-quantitative testing with image J software, amplification with Real-Time Polymerase Chain Reaction (RT-PCR) using norA gene primers. The Mann-Whitney test results gave a value of p = 0.334 (p> 0.05) indicating the suitability between the culture method and the PCR method with the developed protocol in detecting Staphylococcus aureus. The developed method includes the use of base sequences in the norA gene primer, optimization of annealing and extension temperatures, and the concentration of DNA templates used.